Evaluation of Synergistic Interactions Between Cell-Free Supernatant of Lactobacillus Strains and Amikacin and Genetamicin Against Pseudomonas aeruginosa - Aminnezhad, Sargol (Jundishapur J Microbiol, 2015)
BACKGROUND: The indiscriminate use of antibiotics in the treatment of infectious diseases can increase the development of antibiotic resistance. Therefore, there is a big demand for new sources of antimicrobial agents and alternative treatments for reduction of antibiotic dosage required to decrease the associated side effects. OBJECTIVES: In this study, the synergistic action of aminoglycoside antibiotics and cell-free supernatant (CFS) of probiotic (Lactobacillus rahmnosus and L. casei) against Pseudomonas aeruginosa PTCC 1430 was evaluated. MATERIALS AND METHODS: A growth medium for culturing of probiotic bacteria was separated by centrifugation. The antimicrobial effects of CFS of probiotic bacteria were evaluated using the agar well diffusion assay. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated using the micro dilution method. Finally, an interaction between CFS and amikacin or gentamicin against P. aeruginosa PTCC 1430 was examined through the checkerboard method and fractional inhibitory concentration (FIC). Furthermore, CFSs from Lactobacillus strains were analyzed by reversed phase HPLC (RP-HPLC) for antimicrobial compounds. RESULTS: The results showed a significant effect of CFS on the growth of P. aeruginosa. The MIC and MBC of CFS from L. casei were 62.5 µL⁄mL while the MIC and MBC of CFS from L. rhamnosus were 62.5 μL⁄mL and 125 μL⁄mL, respectively. Using the FIC indices, synergistic interactions were observed in combination of CFS and antibiotics. Fractional Inhibitory Concentration indices of CFS from L. casei and aminoglycoside antibiotics were 0.124 and 0.312 while FIC indices of CFS from L. rhamnosus and aminoglycoside antibiotics were 0.124 and 0.56, respectively showing a synergism effect. The results of RP-HPLC showed that CFS of Lactobacillus strains contained acetic acid, lactic acid and hydrogen peroxide (H(2)O(2)). CONCLUSIONS: Our findings indicate that probiotic bacterial strains of Lactobacillus have a significant inhibitory effect on the growth of P. aeruginosa PTCC 1430. The antimicrobial potency of this combination can be useful for designing and developing alternative therapeutic strategies against P. aeruginosa infections.